Eksplorasi Ragam Hias Sasirangan Dengan Teknik Surface Design dan Pewarna Alami - Adilah Zaidah; Yunita Fitra Andriana (IKRAITH-Teknologi, 2022)
The decorative variety of sasirangan fabrics is made with a dyed tie technique where the initialwhite fabric is given a pattern of typical sasirangan motifs and then sews straight according to thepattern that has been made and then tied. Then the cloth that has passed the basting sewing is dyedin dye. The fabrics that are usually chosen for the basic ingredients of sasirangan fabrics includeprimisima cotton, silk fabrics, and synthetic fabrics such as polyester. There are two dyes used forthe application of color to the basic fabric of sasirangan including synthetic or artificial dyes andnatural dyes. Exploration that can be done to create novelty from the decorative variety ofsasirangan is to explore each motif of the sasirangan using surface design techniques includingembroidery techniques, embroidery techniques, and without reducing the authenticity of thesasirangan itself using the tie dye technique.